2017
DOI: 10.1097/md.0000000000009205
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of interleukin-27 assay for the diagnosis of tuberculous pleurisy

Abstract: Background:The concentration of interleukin-27 (IL-27) in pleural effusions was found to be increased in tuberculous pleurisy and several studies have investigated the diagnostic value of IL-27 for tuberculous pleural effusions (TPEs), but the results varied a lot. We conducted the present study to comprehensively evaluate the diagnostic value of IL-27 for TPE.Methods:Primary diagnostic test studies of IL-27 for TPE was searched and identified from databases. The pooled sensitivity, specificity, positive likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
(41 reference statements)
2
10
0
Order By: Relevance
“…TB enhances the production and secretion of IL-27 from antigen presenting cells (APCs) increasing its local concentration 16 . Our results confirm previous studies that have shown the high diagnostic value of IL-27 for the diagnosis of TPE 2,13,17,18 with higher levels of IL-27 in TPE than in non-TPE patients 13,19 . Wu and colleagues reported that the diagnostic accuracy of IL-27 better than that seen with IFN-γ or with ADA showing a sensitivity of 95% and specificity of 97.6% 13 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…TB enhances the production and secretion of IL-27 from antigen presenting cells (APCs) increasing its local concentration 16 . Our results confirm previous studies that have shown the high diagnostic value of IL-27 for the diagnosis of TPE 2,13,17,18 with higher levels of IL-27 in TPE than in non-TPE patients 13,19 . Wu and colleagues reported that the diagnostic accuracy of IL-27 better than that seen with IFN-γ or with ADA showing a sensitivity of 95% and specificity of 97.6% 13 .…”
Section: Discussionsupporting
confidence: 92%
“…Wu and colleagues reported that the diagnostic accuracy of IL-27 better than that seen with IFN-γ or with ADA showing a sensitivity of 95% and specificity of 97.6% 13 . A meta-analysis of IL-27 studies in TPE gave a pooled sensitivity of 0.92 and a specificity of 0.90 19 . In the current study, we found an equally high sensitivity and specificity of IL-27 for the diagnosis of TPE with a sensitivity and specificity significantly higher than that of the other biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Wu and colleagues reported that the diagnostic accuracy of IL-27 was even higher than seen with IFN-γ or with ADA with a sensitivity of 95% and speci city of 97.6% (16). A meta-analysis of IL-27 studies in TPE gave a pooled sensitivity of 0.92 (95% CI, 0.90-0.95) with a speci city of 0.90 (95% CI, 088-0.92) (26). In the current study, we found an equally high sensitivity and speci city of IL-27 for the diagnosis of TPE.…”
Section: Discussionsupporting
confidence: 57%
“…TB enhances the production and secretion of IL-27 from antigen presenting cells (APCs) increasing its local concentration (24). Previous studies have shown the high diagnostic value of IL-27 cytokine for the diagnosis of TPE (2,16,25) with higher levels of IL-27 in TPE than in non-TPE patients (16,26). Wu and colleagues reported that the diagnostic accuracy of IL-27 was even higher than seen with IFN-γ or with ADA with a sensitivity of 95% and speci city of 97.6% (16).…”
Section: Discussionmentioning
confidence: 99%
“…To date, three meta-analyses have reported the diagnostic usefulness of PF IL-27 for TB effusions. 34 36 The most comprehensive one summarized seven studies (mostly from China) with a total of 1157 patients with PEs. 35 The main pooled estimates were as follows: sensitivity 93.8%, specificity 91.7%, LR positive 29.8, LR negative 0.08, and AUC 0.976.…”
Section: Biomarkers Of Pleural Tuberculosismentioning
confidence: 99%